2005
DOI: 10.1177/0145482x0509901107
|View full text |Cite
|
Sign up to set email alerts
|

The National Sports Education Camps Project: Introducing Sports Skills to Students with Visual Impairments through Short-term Specialized Instruction

Abstract: The National Sports Education Camps Project (NSEC), a joint partnership between Western Michigan University and the United States Association of Blind Athletes, provides short-term interventions to teach sports to children with visual impairments. A study comparing 321 students with visual impairments, ranging in age from 8 to 19 years, before and after they participated in the camp found that they knew more about sports, were able to jump and throw farther, held more positive attitudes, and were more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 10 publications
4
46
0
1
Order By: Relevance
“…While it is known that school-age individuals with visual impairments have physical-activity-level deficits compared with sighted peers, few intervention studies have been conducted. The few intervention studies suggest increases in physical activity levels either through new programs (e.g., interventions) or modifications to programs that have been successfully used in the past (Cervantes & Porretta, 2013;Kern & Wolery, 2001;Ponchillia et al, 2005). Although other reasons may apply, one explanation for low numbers of intervention studies may be difficulty in obtaining an appropriate number of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that school-age individuals with visual impairments have physical-activity-level deficits compared with sighted peers, few intervention studies have been conducted. The few intervention studies suggest increases in physical activity levels either through new programs (e.g., interventions) or modifications to programs that have been successfully used in the past (Cervantes & Porretta, 2013;Kern & Wolery, 2001;Ponchillia et al, 2005). Although other reasons may apply, one explanation for low numbers of intervention studies may be difficulty in obtaining an appropriate number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Lieberman et al (2006) Camp participants reported preference for talking pedometers for PA. Total pedometer steps increased during camp. Ponchillia et al (2005) Significant difference was demonstrated in attitudes, knowledge, and skills between precamp and postcamp evaluation. Second-year campers scored significantly higher on precamp PA survey than first-year campers.…”
Section: Study/typementioning
confidence: 96%
“…Among the material selected, eight studies (Table 1) were classified as SET (Aki, Atasavun, Turan, & Kayihan, 2007;Caliskan et al, 2011;Chen & Lin, 2011;Hashemi, Dehghani, Saboonchi, & Roozbahani, 2012;Jazi, Purrajabi, Movahedi, & Jalali, 2012;Mavrovouniotis et al, 2013;Ponchillia, Armbruster, & Wiebold, 2005;Shindo, Kumagai, & Tanaka, 1987), five (Table 2) as LTPA (Boffoli, Foley, Gasperetti, Yang, & Lieberman, 2011;Cervantes & Porretta, 2013;Morelli et al, 2010;Morelli et al, 2011;Robinson & Lieberman, 2007), and five (Table 3) as IS (Fernandez-Vivo, 2002;Joseph, 1984;Lieberman, Butcher, & Moak, 2001;Palazesi, 1986;Wiskochil, Lieberman, Houston-Wilson, & Petersen, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Interventions lasted from 6 to 12 weeks with frequency of two to three times per week and duration of 50-90 min, ranging from a total of 12-54 hr of training. One study had 1 week of consecutive training days with a total of 30 hr of training (Ponchillia et al, 2005). The mode of training included motor-skill training (Aki et al, 2007); goal-ball and movement education (Caliskan et al, 2011); rope-jumping training (Chen & Lin, 2011); gymnastics skill program (Hashemi et al, 2012); balance exercises (Jazi et al, 2012); Greek traditional dances, Pilates, and PE classes (Mavrovouniotis et al, 2013); sports-education program (Ponchillia et al, 2005); and bicycle ergometers (Shindo et al, 1987).…”
Section: Setmentioning
confidence: 99%
See 1 more Smart Citation